(untitled) (Swiss Medical Weekly, 2019)
Although malnutrition is a highly prevalent condition in the inpatient setting, particularly in older patients with multiple morbidities, the medical community has struggled to find efficient, evidence-based approaches for its prevention and treatment. From an evolutionary perspective, illness-related low appetite may be seen as a protective response with the goal of accelerating recovery from disease by improving autophagy. In line with this, earlier trials in the intensive care setting including severely ill patients have demonstrated unwanted effects of overnutrition on patient outcomes. Uncertainties regarding the best approach to the malnourished inpatient in conjunction with a lack of strong trial data may, in part, explain the low level of attention that hospital medical staff have paid to the issue of malnutrition in the non-critical care inpatient setting. The recent Effect of early nutritional support on Frailty, Functional Outcomes and Recovery of malnourished medical inpatients Trial (EFFORT) study, however, has shown that individualised nutritional support reduces severe complications and improves mortality in medical inpatients, with positive effects on functional outcomes and quality of life. These results from a high quality effectiveness trial in conjunction with other studies, such as the NOURISH trial, should prompt us to improve our management of malnutrition in the in-hospital setting. This procedure should start with a systematic screening for risk of malnutrition of admitted patients, effective assessment of nutritional status in multidisciplinary teams including dieticians, nurses and physicians, and the early start of individualised adequate nutritional support of at-risk patients to reach nutritional goals. Understanding the optimal use of nutritional support in patients with acute illness is complex because timing, route of delivery, and the amount and type of nutrients may all affect patient outcomes. Also, particularly for patients on the medical ward, factors such as the logistics of catering, staffing to provide food and support to the patient (i.e., number of nurses and dieticians per patient), motivation/understanding of the patient to eat in defiance of appetite, the empathic human factor of nutritional care, the quality of meals, the taste of supplements, and unnecessary fasting for diagnostic or therapeutic procedures have a strong influence on nutritional care of patients. Further research and clinical trials are required to better understand, step by step, how we can use clinical nutrition best to maximise recovery of our patient and improve their functional status and their quality of life. Such evidence regarding nutritional therapy may allow us to implement personalised nutrition-driven interventions in the future.